Health Preparedness and Narrative Rationality: A Call for Narrative Preparedness - Eivind Engebretsen; Mona Baker (Kerman University of Medical Sciences, 2023)
This conceptual paper argues the need for narrative preparedness, understood as the ability to engage and empathize with peoples' stories and the values they encode, assess them based on the universe in which people live, and acknowledge the narrative rationality of each story - even when it conflicts with the rationality of science. Expanding 'health preparedness' to encompass 'narrative preparedness' complements the ideals of patient centeredness, which are sometimes betrayed when implemented into concrete decisions because the rationality of science that underpins medical practice fails to make sense of patients' stories. We outline the central tenets of narrative preparedness and demonstrate its relevance by discussing various responses to mainstream discourses on COVID-19 as a case in point. We discuss and further develop Fisher's narrative paradigm, which provides a model that complements traditional, scientific rationality with attention to narrative rationality and a radical democratic ground for health political critique. Applying the narrative paradigm to authentic examples of vaccine hesitancy and anti-vaccination demonstrates how closer attention to the way narratives are assessed by different constituencies might help us mitigate some of the sources of resistance and misunderstanding that continue to plague public communication about important medical issues such as pandemics. Health authorities must acknowledge and engage with the stories people believe in and their reasons for doing so. The crucial question for the success of health policy interventions is not only 'what are the facts' but 'how do these facts make sense to people, and why.' To be prepared for the next pandemic, health professionals must learn to engage with people's stories and the processes by which they come to be understood and assessed differently by various constituencies.